Tuning conditions for the amine-functionalization of carbonyls formed in biobased polyfurfuryl alcohol - Delliere, Pierre; Guigo, Nathanael (Giant (Oxford, England), 2024)
Biobased furan resins (furfuryl alcohol based) are functionalized by taking advantage of a side-reaction occurring during its polymerization. The furan ring-opening reactions yields carbonyls which can be functionalized by reaction with primary amines. Light is shed on unexplored parameters impacting the properties of PFA/Amine systems. First, PFA/Amines were prepared using PFA resins at conversion degree between 0.3 and 0.95. Overall, high conversion degrees (0.9 and above) are best suited to produce rigid materials. In addition, a precipitation process may be used to reach high Tg biobased materials (145 °C). Finally, the impact of the amines’ basicity on the properties of PFA/Amines was investigated. The results highlighted that PFAs at conversion degrees above 0.9 are little affected by the basicity. However, the properties of PFA functionalized at lower conversion degrees are strongly affected by the bases, i.e. high brittleness. This can be circumvented by limiting the functionalization degree to 0.25 and below. [Display omitted]